2021
DOI: 10.1038/s41535-020-00300-7
|View full text |Cite
|
Sign up to set email alerts
|

The bulk-corner correspondence of time-reversal symmetric insulators

Abstract: The topology of insulators is usually revealed through the presence of gapless boundary modes: this is the so-called bulk-boundary correspondence. However, the many-body wavefunction of a crystalline insulator is endowed with additional topological properties that do not yield surface spectral features, but manifest themselves as (fractional) quantized electronic charges localized at the crystal boundaries. Here, we formulate such bulk-corner correspondence for the physical relevant case of materials with time… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(10 citation statements)
references
References 61 publications
(81 reference statements)
0
9
0
Order By: Relevance
“…Using first-principles calculations, we have shown that PbTe monolayers [124][125][126] have a nontrivial first-order defect-state response (Appendix F 1), and that the 3D TCI and HOTI SnTe (but not PbTe) [26,31,32,[127][128][129] carries a nontrivial HEND-state dislocation response (Appendix F 2). HEND dislocation states may also be observable in "fragile" topological insulators (TIs) [33,68,96,[103][104][105][106][130][131][132][133][134][135][136][137][138][139][140][141][142][143][144][145][146][147] and obstructed atomic limits [148][149][150][151][152]. Numerous candidate fragile TIs have recently been predicted through high-throughput material searches [128,147], and 3D OAL phases have recently been identified in electrides [153][154][155] and other stoichiometric insulators [156]…”
Section: Data Availabilitymentioning
confidence: 99%
See 4 more Smart Citations
“…Using first-principles calculations, we have shown that PbTe monolayers [124][125][126] have a nontrivial first-order defect-state response (Appendix F 1), and that the 3D TCI and HOTI SnTe (but not PbTe) [26,31,32,[127][128][129] carries a nontrivial HEND-state dislocation response (Appendix F 2). HEND dislocation states may also be observable in "fragile" topological insulators (TIs) [33,68,96,[103][104][105][106][130][131][132][133][134][135][136][137][138][139][140][141][142][143][144][145][146][147] and obstructed atomic limits [148][149][150][151][152]. Numerous candidate fragile TIs have recently been predicted through high-throughput material searches [128,147], and 3D OAL phases have recently been identified in electrides [153][154][155] and other stoichiometric insulators [156]…”
Section: Data Availabilitymentioning
confidence: 99%
“…In this section, we will employ k • p theory to demonstrate the presence of HEND bound states on the corners and ends of crystal defects and flux tubes in two classes of HOTIs: inversion-(I-) symmetric axion insulators (AXIs) [30-33, 92, 93, 96, 97, 102-106, 151, 168-171], which are 3D magnetic insulators with anomalous, gapped 2D surfaces and gapless hinges with 1D chiral modes [7,8,10,13,25,33,92,102,[215][216][217][218], and time-reversal-(T -) and I-symmetric HOTIs [30,96,[99][100][101] with anomalous, gapped (T -symmetric) surfaces [25] and gapless hinges with 1D helical modes (see Appendix B 1 c for more details). We will also show that crystal defects, but crucially not π-flux tubes, bind anomalous HEND states in weak stacks of I-symmetric fragile topological insulators (FTIs) [33,68,96,[103][104][105][106][130][131][132][133][134][135][136][137][138][139][140][141][142][143][144][145][146][147] and obstructed atomic limits (OALs) …”
Section: Defect and Flux Bound States In 3d I-symmetric Insulators Fr...mentioning
confidence: 99%
See 3 more Smart Citations